Impact of rituximab maintenance and maintenance schedule on prognosis in first-line treatment of follicular lymphoma. Retrospective analysis from Czech Lymphoma Study Group (CLSG) database. Issue 5 (3rd May 2016) - Janikova, Andrea; Bortlicek, Zbynek; Campr, Vit; Kopalova, Natasa; Benesova, Katerina; Hamouzova, Jitka; Belada, David; Prochazka, Vit; Pytlik, Robert; Vokurka, Samuel; Pirnos, Jan; Duras, Juraj; et al.
Abstract: Rituximab maintenance (RM) improves time to progression (PFS) in advanced follicular lymphoma (FL), but the impact of various RM schedules remains unknown. This study performed a retrospective evaluation of RM given for up to 2 years vs observation in 319 untreated FL patients (stage II–IV; grade 1–3A) responding to RCHOP induction and a comparison of two different RM schedules (RM8 = eight doses given every 3 months and RM12 = 12 doses given every 2 months). A total of 183 patients received RM and 136 patients were observed; 5-year PFS was better in the RM arm, 74.1% vs 52.3% ( p < 0.001), which was projected in 5-year OS 93.8% vs 87.5% ( p = 0.005). However, 5-year PFS was similar in both the RM8 ( n = 54) and RM12 ( n = 56) arms. In the first line, RM significantly prolongs PFS and OS in FL, but different RM schedules bring a similar benefit.